Effect of Various Types of Sugars on Antioxidant Activity and Physico-chemical Properties of Kombucha Fermented Whey - Suciati, Fitri; Mukminah, Nurul; Fathurohman, Ferdi; Permadi, Edy (State Islamic University of Sultan Syarif Kasim Riau, 2024)
Kombucha or known as SCOBY (Symbiotic Culture of Bacteria and Yeast) is a fermented tea beverage with the addition of sugar then fermented for 7-14 days. Recent studies showed kombucha conceivably used for milk fermentation, such as fermented whey, yogurt, and fermented milks. Sugar is added to kombucha as carbon source for microorganisms in kombucha. Type of sugar, sugar concentration, tea concentration, temperature and incubation time are factors that affect kombucha fermentation. The aims of this study were to determine the effect of various types of sugars on antioxidant activity (2,2-diphenyl-1-picrylhydrazyl (DPPH)) and physicochemical properties (pH, titratable acidity, total dissolved solid, and CIE L* a* b* color space value). The various types of sugars were granulated white sugar (G1), coconut sugar (G2), palm sugar (G3) and no sugar addition as control (G0). Fermented whey using 10% kombucha liquor, 3% kombucha cellulose and 10% sugar addition, whey then fermented at 37oC for 14 hours. Result demonstrated that using of various types of sugars significantly affected antioxidant activity, CIE L*a*b* color space value, pH, titratable acidity, total dissolved solid and vitamin C content. The highest vitamin C content was G3 (0.91±0.05 mg/100ml), kombucha fermented whey using palm sugar. Any type of sugar could be used on kombucha fermented whey, and the highest antioxidant activity (DPPH) was fermented whey kombucha with the addition of coconut sugar (G2) (86.79±10.94%).